A Brief Review on Syntheses, Structures, and Applications of Nanoscrolls - Perim, Eric; Machado, Leonardo Dantas; Galvao, Douglas Soares (Frontiers in Materials, 2014)
Nanoscrolls are papyrus-like nanostructures, which present unique properties due to their open ended morphology. These properties can be exploited in a plethora of technological applications, leading to the design of novel and interesting devices. During the past decade, significant advances in the synthesis and characterization of these structures have been made, but many challenges still remain. In this mini review, we provide an overview on their history, experimental synthesis methods, basic properties, and application perspectives.